Diagnostic Characteristics of Symptom Combinations over Time in Meningitis Patients. Issue 2 (27th December 2013) - Takagi, Hiroshi; Maeno, Takami; Fujita, Tsuneo; Suzuki, Masatsune; Maeno, Tetsuhiro
Abstract : Objective: The aim of this study was to investigate diagnostic characteristics to distinguish bacterial meningitis (BM) from aseptic meningitis (AM) in meningitis patients. Indicators from the initial consultation were combined with a measure of time since the onset of fever. Methods: This was a retrospective chart review. We examined the sensitivity and specificity of the clinical information for BM. The diagnostic characteristics for BM were analyzed by considering the duration of fever for each patient at consultation, together with the presence or absence of changes in their mental status. The study examined 117 inpatients diagnosed with meningitis in their clinical record at the time of admission. The patients were admitted into two emergency hospitals in Japan between 2001 and 2011. Meningitis was defined as the presence of five or more cells per mm 3 of CSF. Results: Twenty‐five patients were diagnosed with BM and 92 patients with AM. There was no single clinical symptom that could distinguish BM from AM in patients suspected of meningitis. The sensitivity and specificity of the clinical information for fever duration and disturbance of consciousness at consultation were 95.0% and 40.3%, respectively, for BM patients with disturbance of consciousness or with duration of fever less than three days. Thus, the proportion of BM patients without disturbance of consciousness for three or more days after fever onset was only 5%. Conclusions: Patients without disturbance of consciousness for three or more days after fever onset are rarely suffering from BM.